Seed Source (Provenance) Variation in Acacia nilotica (L.) Willd. for Salinity Tolerance - Bimlendra, K; Toky, O P; Babber, S (Annals of Arid Zone, 2016)
Ten pravenances (seed saurces) .of Acacia nilotica were screened far seed germination and seedling growth in media having salinity (chlaride or sulphate) from 4 to 16 dS m-I in laboratary conditions. Banaskantha, Chandigarh, Patna, and Bhopal provenances tolerated salinity up ta 8 dS mol at seed germinatian and seedling growth stages, while that of Caimbatore, Baharampur and Dharwad were sensitive even at low (4 dS m-I) level .of salinity. Chloride-dominated salinity was mare injuriaus to A. nilotica than S04-dominated salinity particularly at lower cancentrations. Hawever at higher levels bath sulphate-daminated salinity (16 dS mol) as well as chlaride-daminated salinity, were equally injurious. Pratein and tatal carbahydrate contents were maximum in Banaskantha and Chandigarh provenances. Protein cantent declined significantly as the level of salinity increased, and sugar content showed a reverse trend i.e., it increased with increasing salinity. The study is useful in screening the salinity-tolerant seed saurces at an early stage.